2023
DOI: 10.1001/jamanetworkopen.2023.2716
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Policies, Pandemic Disruptions, and Changes in Child Mental Health and Sleep in the United States

Abstract: ImportanceThe adverse effects of COVID-19 containment policies disrupting child mental health and sleep have been debated. However, few current estimates correct biases of these potential effects.ObjectivesTo determine whether financial and school disruptions related to COVID-19 containment policies and unemployment rates were separately associated with perceived stress, sadness, positive affect, COVID-19–related worry, and sleep.Design, Setting, and ParticipantsThis cohort study was based on the Adolescent Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Available data that have emerged since the onset of the COVID‐19 pandemic indicates that psychological distress may be accelerating at an even more rapid pace in recent years (Harrison, Carducci, Klein, & Bhutta, 2022; Racine et al., 2021), although in promising news, suicide among young people has stabilized or declined in most countries during the pandemic (Pirkis et al., 2022). Furthermore, there has been substantial variability in the impact of the pandemic on youth mental health across countries (Chavira, Ponting, & Ramos, 2022), and increases in psychological distress due to the pandemic among youth are concentrated youth in families financially and otherwise adversely impacted by the pandemic (Hossain et al., 2022; Xiao et al., 2023). Continued focus on understanding the potential short‐ and long‐term consequences of pandemic‐related illness and bereavement, disruptions in socialization and learning, and other effects of the pandemic will be a critical part of mental health surveillance for years to come.…”
Section: Part Iv: Several Novel Risk Factors: the Evidencementioning
confidence: 99%
“…Available data that have emerged since the onset of the COVID‐19 pandemic indicates that psychological distress may be accelerating at an even more rapid pace in recent years (Harrison, Carducci, Klein, & Bhutta, 2022; Racine et al., 2021), although in promising news, suicide among young people has stabilized or declined in most countries during the pandemic (Pirkis et al., 2022). Furthermore, there has been substantial variability in the impact of the pandemic on youth mental health across countries (Chavira, Ponting, & Ramos, 2022), and increases in psychological distress due to the pandemic among youth are concentrated youth in families financially and otherwise adversely impacted by the pandemic (Hossain et al., 2022; Xiao et al., 2023). Continued focus on understanding the potential short‐ and long‐term consequences of pandemic‐related illness and bereavement, disruptions in socialization and learning, and other effects of the pandemic will be a critical part of mental health surveillance for years to come.…”
Section: Part Iv: Several Novel Risk Factors: the Evidencementioning
confidence: 99%
“…We believe the clinical importance of these associations to be substantial for several reasons. First, prior literature 29 , 41 has used the PA and PS scales similarly to assess adolescent mental health correlates. Furthermore, given that stress and well-being are of critical importance in adolescent development and that adolescents experience ACEs at unacceptably high rates, we believe these associations will have major impacts on adolescent mental health at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The economic disruption of shelter-in-place policies may have had substantial negative consequences on the physical and mental health of some populations, particularly children, pregnant women, and those with precarious employment. [21][22][23] A nationwide cohort study of 6030 US children and adolescents aged 10-13 years found that experiencing financial disruptions, despite supportive policies, was associated with a 205.2% increase in perceived stress and a 112.1% increase in sadness. 23 Physical activity levels, especially among medically underserved populations, also declined after the onset of the pandemic.…”
Section: Covid-19-related Morbidity and Mortality Among Us Immigrantsmentioning
confidence: 99%
“…[21][22][23] A nationwide cohort study of 6030 US children and adolescents aged 10-13 years found that experiencing financial disruptions, despite supportive policies, was associated with a 205.2% increase in perceived stress and a 112.1% increase in sadness. 23 Physical activity levels, especially among medically underserved populations, also declined after the onset of the pandemic. 24…”
Section: Covid-19-related Morbidity and Mortality Among Us Immigrantsmentioning
confidence: 99%